Analisis Kualitas Pelayanan Parkir Tepi Jalan Umum di Kota Pekalongan - Herlambang Dwi Anggara; Kismartini Kismartini; Ida Hayu Dwimawanti (Universitas Medan Area, 2022)
This article aims to analyze the quality of public services regarding public roadside parking in Pekalongan City. The problem in this study is focused on parking problems, namely limited land or vehicle parking lots so that people park their vehicles arbitrarily. In addition, it is also due to the actions of several parking attendants who collect parking fees that exceed the provisions and the presence of illegal or unofficial parking attendants who make parking arrangements and collect parking fees. In order to approach these problems, the theoretical references from Zeitaml and Ilosa are used, namely tangible, reliability, responsiveness, assurance, empathy, transparency and security. The data were collected through direct observation and interviews with informants and analyzed qualitatively. This study concludes that the quality of parking services on the edge of public roads is not good. This is indicated by the three dimensions that state that they are not good, namely reliability, responsiveness and assurance, although four dimensions state that they are quite good, namely tangible, assurance, empathy, transparency and security, so that the quality of parking services on the edge of public roads needs to be improved.